2020
DOI: 10.1089/wound.2020.1212
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence, Characteristics, and Prevention Status of Skin Injury Caused by Personal Protective Equipment Among Medical Staff in Fighting COVID-19: A Multicenter, Cross-Sectional Study

Abstract: Objective: To investigate the prevalence, characteristics, and preventive status of skin injuries caused by personal protective equipment (PPE) in medical staff. Approach: A cross-sectional survey was conducted online for understanding skin injuries among medical staff fighting COVID-19 in February 8-22, 2020. Participants voluntarily answered and submitted the questionnaire with cell phone. The questionnaire items included demographic data, grade of PPE and daily wearing time, skin injury types, anatomical si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
235
4
24

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(285 citation statements)
references
References 18 publications
4
235
4
24
Order By: Relevance
“…Researchers found a statistically significant difference in the number of injuries sustained if HCPs exceeded this time frame in PPE. 22 Skin protection under masks is therefore a necessity because shift lengths can be unpredictable based on PPE supplies 23 but also because facial injuries have been noted in shorter shift periods 22 and within 2 hours in this study.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Researchers found a statistically significant difference in the number of injuries sustained if HCPs exceeded this time frame in PPE. 22 Skin protection under masks is therefore a necessity because shift lengths can be unpredictable based on PPE supplies 23 but also because facial injuries have been noted in shorter shift periods 22 and within 2 hours in this study.…”
Section: Discussionmentioning
confidence: 80%
“…A different cross-sectional study 22 (N = 4,306) from China on facial injuries sustained by HCPs when using PPE also identified this 4-hour cut-off time. Researchers found a statistically significant difference in the number of injuries sustained if HCPs exceeded this time frame in PPE.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…[ 1 ] There are studies which showed the prevalence of skin injuries due to heavy sweating and long period of wearing Grade 3 PPE during work. [ 2 ]…”
Section: Problems With Personal Protective Equipmentmentioning
confidence: 99%
“…Prevalence of injuries was higher in males, doctors (as compared to nurses), ones wearing grade 3 PPE, those with daily wearing time >4 hours, those over 35 years old, and the ones with heavy sweating. 4 In another report, prevalence of skin damage was 97.0%, nasal bridge being the most commonly affected site (83.1%). 5 The skin changes associated with protective measures can be seen in four scenarios:…”
mentioning
confidence: 91%